Kaidah Fiqh dan Ushul Fiqh Tentang Produk Halal, Metode Istinbath dan Ijtihad dalam Menetapkan Hukum Produk Halal - Ratna Wijayanti; M Meftahudin (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
The purpose of the discovery of Islamic law must be understood by the mujtahid in order to develop legal thinking in Islam in general and answer contemporary legal issues whose cases are not explicitly regulated by the Koran and Hadith, especially those related to the field of muamalah. In reviewing the matter to be determined by law, the Indonesian Ulema Council Fatwa Commission is based on the Qur'an and Sunnah as its main source. In this context, there are several methods used by the Indonesian Ulema Council Fatwa Commission. First, every Fatwa Decree must have a basis on the Book of Allah and the Sunnah of the Apostle that is not bad, and not contrary to the benefit of the people. Second, if it is not found in the Book of Allah and the Sunnah of the Apostles, the Fatwa Decree should not contradict ijma ', qiyas that mu'tabar, and other legal arguments, such as ihtisan, maslahah mursalah, and saddu al-dzari'ah. Third, before making a decision before deciding on a fatwa, it must first be carefully studied for each problem presented to the MUI at least a week before the trial. If the problem is clear the law (qath'iy) let the commission convey it as it is, and the fatwa will fall after the text is known from the Koran and the Sunnah. Whereas in the case of khilafiyah occurring among the schools of thought, what is stated is the result of tarjih after observing the jurisprudence of muqaran (comparison) using the rules of ushul fiqh muqaran related to scholarship.